2011
DOI: 10.1016/j.mri.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of breast density following tamoxifen treatment evaluated by 3-D MRI: preliminary study

Abstract: This study analyzed the change of breast density in women receiving tamoxifen treatment using 3-D MRI. Sixteen women were studied. Each woman received breast MRI before and after tamoxifen. The breast and the fibroglandular tissue were segmented using a computer-assisted algorithm, based on T1-weighted images. The fibroglandular tissue volume (FV) and breast volume (BV) were measured and the ratio was calculated as the percent breast density (%BD). The changes in breast volume (ΔBV), fibroglandular tissue volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…In several previous publications, we analyzed breast density on nonfat-suppressed images. 15,20,[22][23][24][25] The purpose of the present study is to address the current lack of published studies investigating the difference in breast density measured using fat-suppressed versus nonfat-suppressed sequences. Our breast MRI protocol follows the ACR recommendation and uses fat-suppressed sequence for the dynamic contrast enhanced study.…”
Section: Discussionmentioning
confidence: 99%
“…In several previous publications, we analyzed breast density on nonfat-suppressed images. 15,20,[22][23][24][25] The purpose of the present study is to address the current lack of published studies investigating the difference in breast density measured using fat-suppressed versus nonfat-suppressed sequences. Our breast MRI protocol follows the ACR recommendation and uses fat-suppressed sequence for the dynamic contrast enhanced study.…”
Section: Discussionmentioning
confidence: 99%
“…(1921) Research has not assessed response to treatment with tamoxifen and AI using volumetric density measures on FFDM, though a few studies using MRI suggest volumetric measures may more accurately measure density changes. (22,23) If volumetric density measures from FFDM provide precise estimates of longitudinal change in breast density, they may be used clinically to provide important prognostic information.…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies on estrogen-receptor modulators, 10 assessed change in BD with TAM intervention and included 1 RCT, 10 2 nested CCSs, 8,9 1 CS, 11 and 6 post hoc analyses of RCTs. [33][34][35][36][37][38] The sample sizes of the 10 studies ranged from 16 to 1065 (n = 2877).…”
Section: Resultsmentioning
confidence: 99%
“…About 80% of the studies on TAM and tibolone did not adjust for BD confounders. Two of the studies on estrogen modulators had very small sample sizes, 11,17 and 1 study 99 reported duration of treatment but not dosage administered. There was variability in age, populations, and sample size between studies, thus making comparison of studies difficult.…”
Section: Discussionmentioning
confidence: 99%